American justice 2014 : nine clashing visions on the Supreme Court - Epps, Garrett (EBL-Schweitzer, 2014)
"Garrett Epps reviews the key decisions of the 2013-2014 Supreme Court term, highlighting one opinion or dissent from each Justice to illuminate the political and ideological views that prevail on the Court"--Book Jacket,